Метаболічний вплив метформіну та піоглітазону на тиреоїдний статус, вуглеводний і ліпідний обмін у хворих на гіпотиреоз з інсулінорезистентністю - Москва, Х. А.; Лаповець, Л. Є.; Кіхтяк, О. П. (Clinical Endocrinology and Endocrine Surgery, 2013)
Comparative data between metformin and pioglitazone are described in this paper taking into account their action on thyroid panel, carbohydrate and lipid metabolism in patients with hypothyroidism, established insulin resistance on the base of replacement treatment with levothyroxine. Treatment duration was 6 months, where first 3 months were dedicated to achieve euthyroidism, while the last period of time was given to carry out combination of levothyroxine with pioglitazone or metformin. It was recorded that metformin significantly decreases glycated hemoglobin and fasting glucose. Instead of this, pioglitazone significantly diminished fasting insulin, C-peptide and with resulted descent of HOMA-β and increased Karo index. Comparison of drugs showed that metformin decreased thyroid stimulating hormone and pioglitazone significantly increased the level of free thyroxine and triiodothyronine.